UN MÉTODO DE APROVECHAMIENTO DE ENERGÍA SOLAR EN LA PRODUCCIÓN DEL RABANO (Raphanus sp.) / A METHOD FOR USING SOLAR ENERGY IN RADISH PRODUCTION (RAPHANUS SP) - Legarda Burbano, Lucio; Martínez S., Bernardo; Citelly P., Francisco (Revista de Ciencias Agrícolas, 1973)
Se ha estudiado un método encaminado a aumentar la energía absorbida por el suelo, colocando una delgada capa de carbón vegetal sobre la superficie. El trabajo se llevó a cabo en predios de la Facultad de Ciencias Agrícolas de la Universidad de Nariño, Pasto (0°37’ - 2°43’ N y 79°03’ - 76°47’W). Se emplearon 4 tratamientos: testigo (sin carbón, 500, 1.000 y 1.500 gr. de carbón vegetal por parcela de 1 m2 con 3 replicaciones cada uno). En los tratamientos en que se aplicó carbón, la germinación y el rendimiento de rábano fue mayor, el número de malezas menor, la temperatura mayor y el número de colonias bacteriales aumentaron. ABSTRACT A research was carried out for increasing energy absorbed by the soild, by means of covering the soil surface with a thin organic (wood) carbon layer. This work was performed at the Agricultural Science Faculty fields, University of Nariño, in Pasto (037’ - 2° 43’ N and 79° 03’ – 76° 47 ’W). Four treatments were used: cheek (no carbon), 500, 1.000 and 1.500 gr. of carbon per lot of 1 square meter with three replications in each treatment. Germination, yield, temperature and bacterial colonies increased with carbon application and weed number lessed. It is recommended: to carry out similar works with different carbon quantities and carbon particle sizes to evaluate their influence on soil as well as plant; to study some way of reducing brightness of black color in carbon and increasing its stability to avoid any wash out; and to investigate more on this subject in order to determine which weeds are controlled with the application of this method.